Instrument validity and reliability innovation climate assesment in the organization - Daud, Dalina; Ab. Jalil, Habibah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This pilot study is to verify and check the validity and reliability of assessment instruments construct a climate of innovation within the organization. This instrument consists of five constructs of leadership, ownership, sustainable development, norms diversity and consistency contains 20 items and distributed to 106 pre-university teachers. Data were analyzed using SPSS version 16. The construct validity was determined using factor analysis. The reliability of the instrument is determined using the method of internal consistency with Cronbach alpha values were between 0.72 and 0.83. The instrument was appropriate to be used in investigating the innovative climate in the organization.